2019
DOI: 10.1186/s12964-019-0423-6
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of exosomal CLEC3B in hepatocellular carcinoma promotes metastasis and angiogenesis via AMPK and VEGF signals

Abstract: Background C-Type Lectin Domain Family 3 Member B (CLEC3B), is down-regulated in serum and tumor tissues in different cancers including hepatocellular carcinoma (HCC). However, the functions of CLEC3B in HCC remains elucidated. The aim of this study is to analyze the roles of CLEC3B in HCC. Methods The expression of genes was evaluated by immunohistochemistry, western blot, real-time PCR, enzyme-linked immunosorbent assays, and analysis on TCGA-LIHC database and gene ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 52 publications
(55 reference statements)
2
59
0
Order By: Relevance
“…C-type lectin domain family 3 member B (CLEC3B) encodes tetranectin, a plasminogen kringle-4-binding protein that is located in cell plasma, extracellular matrix and exosomes [8,9]. Tetranectin plays a role in extracellular proteolysis by inducing plasminogen activation, which is associated with tumor invasion and metastasis [8,[10][11][12][13].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…C-type lectin domain family 3 member B (CLEC3B) encodes tetranectin, a plasminogen kringle-4-binding protein that is located in cell plasma, extracellular matrix and exosomes [8,9]. Tetranectin plays a role in extracellular proteolysis by inducing plasminogen activation, which is associated with tumor invasion and metastasis [8,[10][11][12][13].…”
mentioning
confidence: 99%
“…C-type lectin domain family 3 member B (CLEC3B) encodes tetranectin, a plasminogen kringle-4-binding protein that is located in cell plasma, extracellular matrix and exosomes [8,9]. Tetranectin plays a role in extracellular proteolysis by inducing plasminogen activation, which is associated with tumor invasion and metastasis [8,[10][11][12][13]. Moreover, CLEC3B has been reported in multiple cancers, including hepatocellular carcinoma, ovarian cancer, and oral squamous cell carcinoma, but a large number of in-depth studies are still needed to elucidate the molecular mechanism and specific function of CLEC3B in cancer progression [8,[14][15][16][17][18][19].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Consisting with GO analysis, all these genes were predominantly localized in the extracellular compartment according to the information from GeneCards (Stelzer G, 2016). In particularly, C-Type Lectin Domain Family 3 Member B (clec3b) was reported to control cell proliferation in clear cell renal cell carcinoma(Liu et al, 2018) as well as low clec3b in exosomes derived from HCC promoted cell migration, invasion and epithelial–mesenchymal transition(Dai et al, 2019), indicating its contribution to the maintenance of epididymal epithelium. Recent study found that Gelsolin (Gsn) was the major secreted protein in the distal region of the bovine epididymis(Belleannee et al, 2011; Dacheux and Dacheux, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…While the tumors were often founded when the symptoms are obvious, unfortunately, it is often in the malignant advanced stage at this period. On the other hand, the metastasis and recurrent trait of digestive system tumors makes it di cult for conventional treatment programs to exert maximum effectiveness [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%